Visual hallucinations in parkinson's disease: Experience from a portuguese level 3 hospital. (13th April 2021) - Quarenta, J.; Teixeira, T.; Martins, S.
Abstract : Introduction: Parkinson's disease is a neurodegenerative pathology characterized by motor and non-motor symptoms. Hallucinations, especially visual ones, are frequent in this context, with an estimated prevalence of 16 to 40% and associated with a less favorable prognosis. These hallucinations can range from coarse formations to well-defined structures. Objectives: To assess the prevalence of visual hallucionations in a sample of patients diagnosed with Parkinson's Disease. Methods: A cross-sectional descriptive study conducted in a Neurology Department of a Level III portuguese hospital. The sample included patients with Parkinson's Disease observed in an outpatient Neurology appointment between October 1 and December 9, 2019. Results: In the period considered, 100 patients with Parkinson's disease were observed, 65% male, with an average age of 69 years. In 11% of the patients visual hallucinations were reported, of which about half were well defined. All of them had no previous history of visual hallucinations and were under dopaminergic medication. Conclusions: The results show an inferior prevalence when comparing to the literature, albeit still frequent. Therapeutic adequacy has a well recognised impact at a functional level and prognosis. Therefore we stress the importance of a regular follow-up of these patients, recommending a rigorous and comprehensive clinical review.